2022
DOI: 10.3390/agronomy12051083
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Demography of ALS-Resistant Glebionis coronaria as Influenced by Management Factors: Tillage, Allelopathic Crops and Herbicides

Abstract: Glebionis coronaria (L.) Cass. ex Spach is one of the most serious weeds in cereal crops in Northern Tunisia. Our previous studies have confirmed the presence of resistance to ALS-inhibiting herbicides in G. coronaria, showing the evolution of cross-resistance through TS and NTS mechanisms. The purpose of this study was to evaluate the effects of (i) two tillage practices (conventional tillage and reduced tillage), (ii) three known allelopathic crops: Hordeum vulgare L. (Barley), Brassica napus L. (Rapeseed) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In contrast to these results, Hada et al (2020) found that the co-mixtures of aminopyralid + florasulam + 2,4-D and aminopyralid + florasulam provided lower efficacy (85%) against crown daisy than that obtained in our study and by their application of co-mixtures synthetic auxin herbicides 2,4-D + MCPA and dicamba + 2,4-D (respective efficacy of 92% and 94%). In addition, Hada et al (2022) found in another field study that the application of 2,4-D + florasulam on cereals and clopyralid on rapeseed reduced crown daisy densities by 44%, 75%, and 66% in wheat, barley, and rapeseed, respectively, whereas the respective reduction due to dicamba + 2,4-D was 85% and 91% in wheat and barley growth. These efficacy differences could be attributed to differing activity between the synthetic auxin herbicides, differing compatibility in co-formulations with ALS inhibitors, differing susceptibility among the R populations to these herbicides, differing competitive or allopathic ability of the crop species against the weed populations, and differing environmental conditions prevailing during the experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to these results, Hada et al (2020) found that the co-mixtures of aminopyralid + florasulam + 2,4-D and aminopyralid + florasulam provided lower efficacy (85%) against crown daisy than that obtained in our study and by their application of co-mixtures synthetic auxin herbicides 2,4-D + MCPA and dicamba + 2,4-D (respective efficacy of 92% and 94%). In addition, Hada et al (2022) found in another field study that the application of 2,4-D + florasulam on cereals and clopyralid on rapeseed reduced crown daisy densities by 44%, 75%, and 66% in wheat, barley, and rapeseed, respectively, whereas the respective reduction due to dicamba + 2,4-D was 85% and 91% in wheat and barley growth. These efficacy differences could be attributed to differing activity between the synthetic auxin herbicides, differing compatibility in co-formulations with ALS inhibitors, differing susceptibility among the R populations to these herbicides, differing competitive or allopathic ability of the crop species against the weed populations, and differing environmental conditions prevailing during the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Control of corn marigold in winter cereals relies mainly on acetolactate synthase (ALS) inhibitors applied either alone or in mixtures with synthetic auxins (Hada et al 2020(Hada et al , 2021(Hada et al , 2022. Unfortunately, ALS-inhibiting herbicides are the most prone to rapid evolution of target site-mediated resistance, which, in most reported cases, is conferred by a single missense mutation in the ALS gene (Yu and Powles 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation